STRATEGI BISNIS BERBASIS TRANSFORMASI DIGITAL: TANTANGAN DAN PELUANG DALAM MANAJEMEN STRATEGIK MODERN - Elmi Abbas; Uswatun Hasanah; Nurita Andriani (Iqtishaduna: Jurnal Ilmiah Mahasiswa Hukum Ekonomi Syariah, 2026)
Abstract Digital transformation has become a key factor in the sustainability of business operations and modern strategic management. This article analyzes the impact of digital transformation on organizational strategy by reviewing the challenges, opportunities, and the role of human resources and governance in successful technology adoption. The method used is a systematic literature review with a qualitative approach. The analysis shows that digital transformation drives operational efficiency, data-driven decision-making, continuous innovation, and the formation of competitive advantage. However, it also presents challenges such as internal resistance, low digital literacy, cybersecurity risks, and data governance complexity. The success of digital transformation is determined by the harmonious integration of technology, human resource capabilities, adaptive organizational strategies, and the implementation of modern strategic management, which includes digital leadership, adaptive organizational culture, digital performance monitoring, and change management. These findings confirm that organizations that are able to manage digital transformation holistically will be better prepared to face market dynamics, increase competitiveness, and ensure business sustainability in the complex digital era. Keywords: digital transformation, modern strategic management, digital leadership, digital literacy, competitive advantage.